The past, present and future of imaging in multiple sclerosis. - Ramli, N.; Rahmat, K.; Azmi, K.; Chong, H.T. (2010)
Despite technological advances in imaging, multiple sclerosis (MS) remains a clinical diagnosis that is supported, but not replaced, by laboratory or imaging findings. However, imaging is essential in the current diagnostic criteria of MS, for prediction of the likelihood of MS for patients with clinically isolated syndromes, correlation with lesion pathology and assessment of treatment outcome. This article gives an overview of imaging in MS with particular emphasis on the role of MRI in various diagnostic imaging criteria. Novel imaging for MS using 3 Tesla field strengths, magnetization transfer imaging, diffusion tensor imaging, magnetic resonance spectroscopy and cell-specific contrast will be reviewed.